Functional Olfactory Nerve Regeneration Demonstrated by Thallium-201 Olfacto-Scintigraphy in Patients with Traumatic Anosmia: A Case Report - Rong-San Jiang; Yu-Yu Lu (Case Reports in Otolaryngology)
Head trauma is one of the most common etiologies of olfactory dysfunction. It is difficult to use either the olfactory function test or magnetic resonance imaging to directly assess the course of damage to olfactory nerves. Thallium-201 (201Tl) olfacto-scintigraphy has been shown to be an able means for objectively assessing the olfactory nerve transport function. It is expected to be used to evaluate olfactory nerve regeneration after damage to the olfactory nerves. However, no such result has been reported. We present a patient who lost his olfactory function after experiencing head trauma. When his olfactory function remained anosmic, a 201Tl olfacto-scintigraphy showed no migration of 201Tl from the nasal mucosa to the olfactory bulb. After treatment with medicines and olfactory training, his olfactory function improved. A second 201Tl olfacto-scintigraphy showed an increased migration of 201Tl from the nasal mucosa to the olfactory bulb.